LIMBAH PLASTIK POLYETHYLENE TEREPHLATE SEBAGAI BAHAN CAMPURAN UNTUK PEMBUATAN BATU BATA RAMAH LINGKUNGAN - Masdania Zurairah; Moyos Muhammad Yusuf (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
Research has been done on plastic waste as a mixed material in the manufacture of bricks.The plastic waste used is Polyethylene Terephlate (PET) mineral water bottle plastic waste.A comparison is made between plastic and aggregate, with the ratio of plastic: aggregate, namely 50%: 50% is A1, 60%: 40% is A2, and 70%: 30% is A3.The more PET plastic waste, the smaller the volume shrinkage with the results A1 = 1268.65 grams, A2 = 1257.08 grams, A3 = 1246.17 grams where the initial weight is 1,500 grams.The water absorption capacity occurs that the greater the water absorption PET, the smaller the water absorption capacity so that the dry weight is obtained A1 = 1257.08 grams, A2 = 1246.17 grams and A3 = 1246.17 grams.